The Palgrave Handbook of Ageing and Physical Activity Promotion (Springer International Publishing, 2018)
The ageing of our population is a key societal issue across the globe. Although people are living longer, they need to be living longer in good health to continue to enjoy quality of life and independence and to prevent rises in health and social care costs. This timely and ground-breaking volume will provide an up-to-date overview of the factors that promote physical activity in later life. Despite advances in the fields of gerontology and geriatrics, sports and exercise science, sociology, health psychology, and public health, knowledge is largely contained within disciplines as reflected in the current provision of academic texts on this subject. To truly address the present and substantial societal challenges of population ageing, a multidisciplinary and collaborative approach is required. This handbook will inform researchers, students, and practitioners on the current evidence base for what physical activities need to be promoted among older people and how they can be implemented to maximise engagement. This handbook will be an invaluable resource for researchers, practitioners, policy makers, and students across the social sciences.